2017
DOI: 10.17511/ijmrr.2017.i02.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Escitalopram on C reactive protein in patients of depression

Abstract: Objective: To study the anti-inflammatory activity of Escitalopram in newly diagnosed patients of depression. Materials and Methods: 100 Newly diagnosed patients of Depression as per ICD 10 (International classification of diseases) DCR (Diagnostic criteria for research) were selected for study after applying strict inclusion and exclusion criteria. Baseline Hamilton depression rating scale (HAMD) and baseline C reactive protein (CRP) was assessed and antidepressant treatment was started. After 8 weeks, again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(10 reference statements)
2
0
0
Order By: Relevance
“…In our study the baseline hsCRP level was significantly lower in responders when compared to non-responders, that is, patients with low hsCRP levels tended to respond better to SSRIs. This was in accordance with a few studies which revealed that increased CRP was indicative of a poorer treatment response to antidepressant therapy [51‒53, 56, 57]. This suggests that hsCRP can be a de­sirable marker which can be used to predict response to SSRIs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study the baseline hsCRP level was significantly lower in responders when compared to non-responders, that is, patients with low hsCRP levels tended to respond better to SSRIs. This was in accordance with a few studies which revealed that increased CRP was indicative of a poorer treatment response to antidepressant therapy [51‒53, 56, 57]. This suggests that hsCRP can be a de­sirable marker which can be used to predict response to SSRIs.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, pretreatment hsCRP levels predicted response to SSRIs. In addition to a similar outcome, a study also found a positive correlation between baseline HAM-D score and baseline CRP [57], but we found no significant association between baseline hsCRP and severity of depression nor duration of illness.…”
Section: Discussionsupporting
confidence: 72%